Exorcising Intersex and Cripping Compulsory Dyadism - Orr, Celeste E. (Université d'Ottawa / University of Ottawa, 2018)
Using hauntology as a linchpin, this dissertation explores the undertheorized connection between intersex and disability. Building on important feminist research in the fields of intersex, queer, disability, crip, and hauntology studies, I ask, how do we understand and reconcile the contested meanings, responses to, and effects of intersex? Intersex is “a perpetually shifting phantasm” (Holmes 2002: 175), yet intersex is typically represented and treated as innate disorder, disability, or disease by medical professionals. That said, many intersex people appear to distance from disability. By engaging intersex studies with feminist disability and crip theories, however, I demonstrate that an intersex politic and intersex studies must be rooted in a disability politic and disability studies. Through a feminist disability and crip lens, I conduct a textual and critical discourse analysis of three case studies of interphobic violence or, what I term, “compulsory dyadism,” meaning the instituted cultural mandate that people cannot have intersex traits or house the “spectre of intersex” (Sparrow 2013: 29); such a spectre must be exorcised. The three case studies include nonconsensual medical interventions, sport sex testing, and employing reproductive technologies to select against intersex variations. My analyses of these case studies produce three important observations. First, intersex is presently and effectively being integrated into conventional notions of disability; second, ableist logics underpin interphobic violence; and third, compulsory dyadism is intertwined with, or is an iteration of, compulsory able-bodiedness. In recognizing this interconnection, theorizing intersex and disability together is not merely beneficial, doing so is necessary. Ultimately, my dissertation interrogates and extends questions of the ever-shifting categorization of body-minds, culturally mandated ways of being, and (the haunting effects of) pathologization. I apply pressure to the academic field of intersex studies as well as intersex activist and advocate communities to center disability in discussions concerning intersex human rights and interphobia.
Keywords: intersex studies; disability studies; crip theory; queer theory; compulsory dyadism; compulsory able-bodiedness; compulsory heterosexuality; hauntology; intersex genital mutilation (IGM); medical malpractice; eugenics; reproductive technologies; preimplantation genetic diagnosis; sport sex testing; sport sex segregation; sport dis/ability segregation; activism; curative violence